Developing Physics Comprehensive Contextual Teaching Material (PhyCCTM) to Improve the Problem Solving Skill - Zaini, Muhammad (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2020)
AbstractÂ Development of teaching materials in learning physics is something that is needed and implanted continuously. Thus, the development of teaching materials has an important role in learning physics to complete the nature of physics it self. Physics learning is mostly only taught based on the theories in the book, so it is difficult for students to imagine the physical phenomena that occur. One effect is the low ability of students in problem solving. This study aims to produce PhyCCTM teaching materials that can improve problem solving skills and find out the improvement of studentsâ€™ problem solving abilities using PhyCCTM teaching materials. This research is a research and development. The development procedure refers to the development adapted from the 4D model which consists of four stage namely defining, designing, developing, and distributing. Content validation was carried out by four lecturers and seven physics teachers. The Trials was conducted at school by applying the quasi-experimental method and using the control group pretest and posttest design. The trial was conducted by taking two classes as the experimental and control class. Improvement and differences in the result of studentsâ€™ problem solving abilities in the experimental and control groups were done by t-test.The research results obtained are PhyCCTM teaching materials to improve problem-solving abilities suitable for use with the category of â€œGoodâ€ and PhyCCTM able to improve studentsâ€™ ability to solve problems with sig. (2-tailed) ofÂ 0,000. The conclusion obtained from this study is that PhyCCTM teaching materials developed are feasible to use and can improve studentsâ€™ ability to solve problems.Keywords: PhyCCTM, Problem Solving Skill